ENERGY SECURITY AS A LEGAL CATEGORY (Journal of actual problems of jurisprudence, 2020)
The article analyzes the practical approach to the concept of “energy security”. Based on the study of the concept of energy policy of countries that are importers, exporters and countries through which energy resources transit, an attempt is made to identify common approaches to the content of this concept at the present stage. Highlighting that the common denominator of practical approaches is availability, safety and price, the author comes to the conclusion about the complex nature of this phenomenon, which depends on many criteria. At the same time, according to the author, the problem of energy security is one of the most important areas of modern theory and practice of economic, social and military security. The author concludes that energy policy largely determines the issues of domestic and foreign policy of most countries of the world and thus is the subject of dialogue. The analysis of the current international legislation has shown the absence of a single formulation of the concept under study, which is based, in our opinion, on the difference of approaches and the versatility of its content. At the same time, the authors point to the need for scientific analysis of this concept from the legal point of view, which is justified by the need for constant regulatory support of the conditions necessary to ensure energy security in the country and in the world. Key words: security, law, energy, security, identity, individual, legal entity.